2020
DOI: 10.5603/ah.a2020.0002
|View full text |Cite
|
Sign up to set email alerts
|

Features of hemodynamic and metabolic disorders in obese patients with resistant hypertension

Abstract: Background. The aim was to establish the features of hemodynamic and metabolic parameters in obese patients with true and pseudo-resistant arterial hypertension (AH). Material and methods. The study included 200 patients with uncontrolled AH and obesity. Patients were initially prescribed dual antihypertensive therapy. Those patients who did not reach target blood pressure (BP) levels after 3 months on dual therapy were additionally prescribed a third antihypertensive drug. Of the 98 patients who were assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…4). It was found that, similar to the results of our previous study, obese patients with true resistance had significantly lower BMI (p < 0.05) and higher levels of aldosterone (p < 0.05) compared with pseudo-resistant patients [10]. At the same time, in this work, new data were obtained on the difference in the levels of SBP (significantly higher with true resistance) and LDL-C (significantly lower with true resistance), which was not obtained with a smaller sample of patients with a narrower range of pseudo-resistance factors.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…4). It was found that, similar to the results of our previous study, obese patients with true resistance had significantly lower BMI (p < 0.05) and higher levels of aldosterone (p < 0.05) compared with pseudo-resistant patients [10]. At the same time, in this work, new data were obtained on the difference in the levels of SBP (significantly higher with true resistance) and LDL-C (significantly lower with true resistance), which was not obtained with a smaller sample of patients with a narrower range of pseudo-resistance factors.…”
Section: Resultssupporting
confidence: 88%
“…Considering the fact that, in comparison with our previous work [10], the group of patients with resistant hypertension was expanded, including the addition of patients with pseudo-resistance of various origins, it was important to determine whether this affected the emergence of any new differences be-tween the indicators (Tab. 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low-grade inflammation and dysfunction of oxidative and antioxidant processes, which underlie the development of many chronic non-communicable diseases and are common in patients with SH [21][22][23][24], were found in patients with a combined course of hypertension and SH in our study. Interestingly, SIRT1, which plays a protective role in the development of oxidative stress [25], was elevated in patients with HTN and SH.…”
Section: Discussionmentioning
confidence: 51%